Protocolo de bioseguridad para prevenir el contagio de Covid- 19, en el Mercado Mayorista sección cárnico de la Ciudad Riobamba, 2020. - Quitio Mullo, Cristian Fernando (2021)
The objective of this work is to elaborate a biosecurity protocol manual for the prevention of COVID-19 infection in the meat wholesale market section of the city of Riobamba, the type of research used was scientific observation, which allowed gathering essential data such as the state of the infrastructure in which the meat section of the EP EMMPA is located, In addition to the use of descriptive research, which made it possible to draw up a logbook with data and a record of the personnel, the section where they are located and thus be able to hypothesize the real problem in order to provide help or a favorable solution, and documentary research on the subject of Covid-19. The manual seeks to provide information regarding the mode of transmission of the virus, the respective biosafety standards to be taken into account, thus preventing the transmission and spread of Covid-19, being the lack of information a risk for contagion. The research made it possible to know the product and dosage necessary for the cleaning of the materials used, in addition to the biosafety clothing used, the priority of using alcohol with a minimum of 70% concentration, the footbath, money disinfection tray, the signage of the distancing, in this way the working staff has knowledge of what actions to take against this virus, its means of propagation, the symptoms, which allowed them to take care and better perform their work functions.